PENGARUH KEPADATAN KANDANG TERHADAP KONSUMSI RANSUM, PERTAMBAHAN BERAT TUBUH, DAN KONVERSI RANSUM BROILER UMUR 14-28 HARI DI CLOSED HOUSE - Siti Mariyam, Syahrio Tantalo, Riyanti, dan Dian Septinova (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2020)
This research aimed : 1) to investigate the effect of stocking density on feed consumption, body weight gain, and feed conversion rate of broiler aged 14—28 days in closed house; 2) to determaine the best stocking density on feed consumption, body weight gain, and feed conversion ratio of broiler aged 14—28 days in closed house. This research was conducted in closed house of PT. Charoen Pokphand (Kandang Bandara 2) located in Bangun Sari area of Way Sari village, Natar district, South Lampung regency. This research was conducted for 28 days, with rearing broiler from day 1st—13th was without treatment, and then from day 14th—harvest with treatments, that was conducted in April 2019—May 2019. This research used completely randomized design with 4 treatments (15, 17, 19, and 21 stocking density of chickens m-2) and 5 replications. Data obtained was analyzed using analysis on variance at 5% levels of significance and followed by Duncan’s Multiple Range Test. Results showed that different stocking density of 15, 17, 19, and 21 chickens m-2 affected (P<0.05) on feed consumption (with feed consumption of broiler of stocking density of 15 chickens m-2 was significantly (P<0.05) lower than those of 17, 19, and 21 chickens m-2), but it did not affect (P>0.05) on body weight gain and feed conversion ratio of broiler in closed house. Keywords: Body weight gain, Closed house, Feed consumption, Feed convertion rate, Cage density